Emphysematous pyelonephritis in patient with hemophagocytic lymphohistiocytosis: A case report - Singgih, Nicholas Andrian; Oktaviani, Jacinda Risha; Secodiningrat, Raden Honggo Pranowo Sampurno; Manuputty, Egi Edward (Indian Journal of Case Reports, 2024)
Emphysematous pyelonephritis (EPN) and hemophagocytic lymphohistiocytosis (HLH) are rare, fatal illnesses. The presence of both at once in a patient is extremely rare. The number of reported cases of EPN is